A Study on Teachers’ Digital Empowerment - Buket Akkoyunlu; Yılmaz Soylu (Türk Kütüphaneciliği)
Technological development has flourished lately and its role in education might play a key role in young people’s social, educational, and professional life. Educators must teach young people relevant information and skills not only to give them a chance to explore and understand the world around them but also to familiarize them with digital technologies. But before we can educate young people we must empower teachers using digital technology. Because teachers who use digital technologies appropriately are not only good models but also help students develop positive attitudes towards such technologies. Considering that, the purpose of this study is to determine the levels of teachers’ digital enpowerment. Descriptive methods were used in this study to determine current level of teachers’ digital empowerment. It was found that teachers have average levels of digital enpowerment. Looking closer at sub-categories, it was found that their awareness and motivation levels were higher, however, technical access and empowerment levels were average. Comparing males and females showed that both teachers had high scores on awareness and technical access but motivation, empowerment, and over all males and females were roughly average. When subcategories of digital empowerment was analyzed according to teachers’ specialties, it showed that Computer and Science teachers’ had high scores on awareness, motivation, technical access empowerment and overall average. However, Social Science, Turkish and Language teachers had high scores on awareness and motivation, but technical access, empowerment and overall average were average.